Steady as she goes? A bibliometric analysis of L2 vocabulary research in 1987 - Paul Meara (LingBaW)
This paper uses a co-citation analysis to examine the research on L2 vocabulary acquisition that was published in 1987. This year is surprisingly volatile compared with the previous year, 1986, with a very large number of new sources appearing in the maps, and many sources identified in previous years losing their influence in the research papers that make up the 1987 data set. The paper also reports a larger analysis of all the work that appeared in a five year window from 1983–1987. This larger data set is not quite as volatile as the smaller 1987 data set, but it suggests that some sources who dominated the co-citation maps in earlier years are losing their influence.